(untitled) (Research, Society and Development, 2021)
The aim of this study is to present scientific evidence based on a systematic literature review (PRISMA) answering the guiding question: Are swallowing and nutritional aspects affected in patients with oropharyngeal cancer? The search for articles was carried out in the databases Scielo, Lilacs, Pubmed, Scopus, Bireme and Web Of Science, there was no restriction on location, period and language. For the selection of studies, the combination based on the Medical Subject Heading Terms (MeSH) was used. In addition, a search for gray literature was carried out on Google Scholar. 132 articles with potential for inclusion were identified, 3 of which met the defined inclusion criteria and the guiding question. Patients with head and neck cancer, who presented complaints of dysphagia had decreased swallowing efficiency, in addition to longer transit, presence of residue and aspiration, compared to those who did not complain. The nutritional gain via enteral, in some cases, is not enough, requiring alternatives, such as venous hyperalimentation. The ability to perceive the function of swallowing can be useful for self-monitoring changes in the state of dysphagia during swallowing therapy. Adding swallowing therapy does not improve normal food intake but accelerates the recovery of swallowing function. Venous hyperalimentation is a viable and efficient alternative in some cases, to meet the nutritional needs of cancer patients in which there the oral feeding is not possible and in the face of problems with enteral nutrition.